Net benefits of smallholder dairy cattle farms in Senegal can be significantly increased through the use of better dairy cattle breeds and improved management practices - Marshall, Karen; Salmon, Gareth R.; Tebug, Stanly Fon; Juga, J.; MacLeod, M.; Poole, Elizabeth J.; Baltenweck, Isabelle; Missohou, A. (American Dairy Science Association, 2020)
Senegal, located in West Africa, is an example of a low- to middle-income country where the government has prioritized improving livestock production self-sufficiency, with a strong focus on dairy. Among other initiatives, the use of exotic dairy cattle has been promoted, despite no evidence for the potential livelihood benefits (or otherwise) to smallholder farmers on adopting the new genetics. The current work fills this evidence gap by performing a farm-level economic study comparing the keeping of different breed and cross-breed types of dairy cattle under different management levels. Data for the study were obtained by monitoring 220 smallholder dairy cattle farms, with a combined cattle population of about 3,000 animals, over an almost 2-yr period. Findings of the study suggest that the most net-beneficial and cost-beneficial dairy cattle enterprise that could be used by the smallholder farmers was to keep crossbred indigenous zebu by exotic Bos taurus animals under management standards that are considered good compared with local standards. This dairy enterprise type was 7.4-fold more net beneficial and had a 1.4-fold more favorable cost-benefit ratio than the traditional system of keeping indigenous zebu animals under poor (low-input) management. Interestingly, the keeping of (near) pure B. taurus dairy cattle resulted in the highest milk yields and thus benefit from milk, but was not the most net beneficial due to the high costs of keeping these animals, particularly in terms of feed. We also found that increasing the management level of any of the breed or cross-breed types under consideration, including the indigenous zebu animals, resulted in an increased net benefit of 2.2- to 2.9-fold. Results of this economic analysis are discussed as part of a broader trade-off analysis, resulting in recommendations to strengthen the Senegal dairy sector. The combined intervention of improved dairy cattle genetics and management is considered a promising intervention to improve livelihoods of the rural poor as well as livestock production self-sufficiency for Senegal; some other system constraints are addressed.